“Managing” CorporateCommunity Involvement - van der Voort, Judith M. (Journal of business ethics, 2009)
In academic research, many attempts have been undertaken to legitimize corporate community involvement by showing a business case for it. However, much less attention has been devoted to building understanding about the actual dynamics and challenges of managing CCI in the business context. As an alternative to existing predominantly static and top-down approaches, this paper introduces a social movement framework for analyzing CCI management. Based on the analysis of qualitative case study data, we argue that the active role of employees pressuring for CCI policies and practices, as well as the organization audience responses to their efforts, are at the core of the challenges involved in managing CCI. These challenges also pose limits to how far CCI can be extended to a “business as usual” activity.